Motor functional recovery after rehabilitation following parasagittal meningioma surgery: A prospective interventional study from Vietnam - Thuy, Nguyen Thi Thu; Giang, Ha Thi Huong; Lien, Nguyen Thi Kim (Tạp chí Nghiên cứu Y học, 2026)
This prospective single-group interventional study aimed to evaluate motor functional recovery and identify factors associated with rehabilitation outcomes in patients following parasagittal meningioma surgery. Thirty patients presenting with postoperative motor weakness after tumor resection participated in a standardized 2-week inpatient rehabilitation program combining physical and occupational therapy, followed by outpatient continuation. Motor and functional outcomes were assessed using the Motor Assessment Scale (MAS), Manual Muscle Testing (MMT), and Functional Independence Measure (FIM) at baseline, 1 month, and 3 months post-intervention. Significant improvements were observed across all scales, with MAS increasing from 30.1 ± 10.9 to 37.8 ± 8.5 and 39.2 ± 8.4, MMT from 126.3 ± 19.8 to 136.0 ± 20.2 and 141.6 ± 18.8, and FIM from 85.0 ± 29.6 to 93.4 ± 20.3 and 99.7 ± 18.6 (p < 0.05 for all comparisons). Generalized Estimating Equations analysis revealed that age, peritumoral edema and preoperative motor weakness were not significant predictors. These findings support the role of early, targeted rehabilitation as a beneficial component of postoperative care for patients with parasagittal meningioma. Larger controlled studies with longer follow-up are required to better delineate recovery trajectories and clarify factors influencing rehabilitation outcomes in this population.